Prevalence of prehypertension and its associated factors among adults visiting outpatient clinic in Northeast Malaysia. Issue 5 (October 2018) - Rafan, Siti NurHani; Zakaria, Rosnani; Ismail, Shaiful Bahari; Muhamad, Rosediani
الملخص: أهداف البحث: "ما قبل فرط ضغط الدم" يشير إلى ضغط الدم ١٢٠ - ١٣٩ مم زئبق الانقباضي أو ٨٠ - ٨٩ مم زئبق الانبساطي. إن تقدير معدل انتشار "ما قبل فرط ضغط الدم" في السكان وتحديد العوامل المرتبطة بالقلب والأوعية الدموية مهم لتقليل الوصول لفرط ضغط الدم. تهدف هذه الدراسة لتحديد معدل انتشار "ما قبل فرط ضغط الدم" وعوامله المرتبطة بين الماليزيين البالغين. طرق البحث: في ٢٠١٥ أجريت دراسة مستعرضة بين البالغين في العيادات الخارجية شمال شرق ماليزيا. أجريت مقابلة وجها لوجه باستخدام النسخة الملاوية والإنجليزية لاستبانة مراقبة (الأمراض غير المعدية) الماليزية. تحوي هذا الاستبانة على المعلومات الاجتماعية والديموغرافية، وحالة نمط الحياة والبيانات الأنثروبومترية. كما تم قياس ضغط الدم ثلاث مرات بواسطة مقياس ضغط الدم، تم تجاهل قيمة القياس الأولى وتم تسجيل متوسط ضغط الدم من القراءتين الأخرى للمزيد من تحليل البيانات. تم عمل الانحدار اللوجستي لتحليل العوامل المرتبطة لما قبل فرط ضغط الدم. النتائج: انضم ١٥١ بالغا لهذه الدراسة بمعدل انتشار "ما قبل فرط ضغط الدم" ٣٧.١٪. كانت العوامل المرتبطة مع ما قبل فرط ضغط الدم في هذه الدراسة العمر، الذكور ومحيط الخصر غير الطبيعي كما تم تسجيله بواسطة تحليل الانحدار اللوجستي المتعدد. الاستنتاجات: في هذه الدراسة معدل انتشار ما قبل فرط ضغط الدم أعلى من معدل انتشار فرط ضغط الدم المنشور في الأدبيات. العمر، الجنس ومحيط الخصر غير الطبيعي هي عوامل مرتبطة ذات دلالة تؤدي إلى "ما قبل فرط ضغط الدم". Abstract: Objectives: Prehypertension refers to a systolic blood pressure of 120–139 mmHg systolic or a diastolic blood pressure of 80–89 mmHg. Estimation of the prevalence of prehypertension in the population and identification of cardiovascular associated factors are important to reduce progression to hypertension. This study aimed to determine the prevalence of prehypertension and its associated factors among Malaysian adults. Methods: In 2015, a cross-sectional study was conducted among adults visiting an outpatient clinic in Northeast Malaysia. Face-to-face interviews were conducted using Malay and English versions of the Malaysia Non-Communicable Disease surveillance questionnaire. This instrument captured information about sociodemographic, lifestyle status, and anthropometric data. Blood pressure was measured three times with a sphygmomanometer, the first measurement value was discarded, and an average of blood pressure from the second two readings was recorded for further data analysis. Logistic regression was performed to analyse factors associated with prehypertension. Result: A total 151 adults participated in the study, and the prevalence of prehypertension was 37.1% (95% confidence interval [CI]: 29.29, 44.69). Factors associated with prehypertension in this study were age (adjusted odds ratio [aOR] = 1.06 95% CI: 1.02, 1.11; p  = 0.007), male sex (aOR = 4.44 95% CI: 1.58, 12.44; p  = 0.005), and abnormal waist circumference (aOR = 31.65 95% CI: 11.25, 89.02; p  < 0.001) as determined by multiple logistic regression analysis. Conclusion: In this study, the prevalence rate of prehypertension of 37.1% is higher than that of hypertension reported in the literature. Age, male sex, and abnormal waist circumference are significant associated factors that lead to prehypertension.